Market reaction Analysis on Stocks Listed in the SRI-KEHATI Index - Amalia Astari, Nurul; Wijayanti, Risna (Jurnal Management Risiko dan Keuangan, 2025)
This study aims to understand investor behavior toward sustainable investment drives the need to analyze market reaction surrounding changes in the SRI-KEHATI Index, a benchmark for ESG-oriented stocks in Indonesia. This study aims to assess market reaction in response to additions and removals of stocks from the index during the 2022–2024 period. Employing an event study method with an 11-day observation window (t–5 to t+5), the analysis uses Cumulative Average Abnormal Return (CAAR) as proxies for market reaction. The study examines 42 stocks affected by index composition changes over five evaluation periods. Results show that stocks included in the index experienced positive CAAR, suggesting positive sentiment and buying pressure. In contrast, excluded stocks displayed negative CAAR, indicating negative sentiment and selling activity. These outcomes align with signaling theory, where inclusion in the index signals positive prospects to investors. The findings imply that SRI-KEHATI Index revisions contain meaningful information that shapes investor perceptions and trading behavior, reinforcing the role of ESG indices in influencing capital market dynamics.